1997
DOI: 10.1210/endo.138.3.4979
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Ligand Binding Specificity and Transcript Tissue Distribution of Estrogen Receptors α and β

Abstract: The rat estrogen receptor (ER) exists as two subtypes, ER alpha and ER beta, which differ in the C-terminal ligand binding domain and in the N-terminal transactivation domain. In this study we investigated the messenger RNA expression of both ER subtypes in rat tissues by RT-PCR and compared the ligand binding specificity of the ER subtypes. Saturation ligand binding analysis of in vitro synthesized human ER alpha and rat ER beta protein revealed a single binding component for 16 alpha-iodo-17 beta-estradiol w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

31
749
6
39

Year Published

1997
1997
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 3,177 publications
(825 citation statements)
references
References 36 publications
31
749
6
39
Order By: Relevance
“…Previous studies have indicated that the iso¯avonoid genistein shows a higher a nity for ERb (Barkhem et al, 1998;Kuiper et al, 1997). 293 cells were cotransfected as before with the ERE-reporter plasmid and ERa or ERb expressing plasmids and treated with increasing amounts of genistein.…”
Section: Erb Promotes the Agonistic Effect Of Genisteinmentioning
confidence: 99%
“…Previous studies have indicated that the iso¯avonoid genistein shows a higher a nity for ERb (Barkhem et al, 1998;Kuiper et al, 1997). 293 cells were cotransfected as before with the ERE-reporter plasmid and ERa or ERb expressing plasmids and treated with increasing amounts of genistein.…”
Section: Erb Promotes the Agonistic Effect Of Genisteinmentioning
confidence: 99%
“…In a cell culture assay, amphioxus SR is not as responsive to E2 as is human ERα; the SR requires about 100 nM E2 to activate gene transcription to 50% of the maximum response [13]. This is substantially higher than 0.2 nM E2 for the Kd of E2 for human ERα [15].…”
Section: Discussionmentioning
confidence: 92%
“…A surprising finding is that amphioxus ER does not bind steroids [13,14]. In contrast, amphioxus SR is activated by estradiol [13], although at an estradiol concentration that is more than 100-fold higher than found for binding to human ERα [15]. Unexpectedly, the SR does not bind 3-ketosteroids [13], despite the clear phylogenetic clustering of the SR with the GR, MR, PR and AR [13,14].…”
mentioning
confidence: 91%
“…Thus, estrogen attenuates the antidiuretic effect of VP. This may reflect activation of ERα, because although both ERα and ERβ have been localized to the kidney [100], ERα is most prominent [33] (See Table 2). ERα is present in the collecting duct in rat kidney [100], the antidiuretic site of VP, and estrogen regulation of gene expression is dependent on ERα in the kidney [30].…”
Section: Effects On Vp-induced Antidiuresismentioning
confidence: 99%